2013
DOI: 10.1039/c3dt50780g
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and photometric characterization of K+ compensated CaMoO4:Dy3+ nanophosphors

Abstract: A series of CaMoO4 phosphors doped with trivalent dysprosium (Dy(3+)) and codoped with potassium (K(+)) ions were prepared by hydrothermal method. The nanostructures of the as-synthesized phosphors were investigated by X-ray diffraction (XRD). The results reveal that the obtained powder phosphors are single-phase scheelite structure with tetragonal symmetry and the crystallite size is in the range of 10-60 nm. The emission spectra show a bright yellow emission at 576 nm and blue emission at 487 nm. As a charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(95 citation statements)
references
References 18 publications
(13 reference statements)
3
92
0
Order By: Relevance
“…The possible non-radiative channels explained in Fig. 8 41,45,53 Further, the luminescence intensity ratio of yellow to blue (Y/B) is essential for white-light emission. The calculated (Y/B) ratio for the optimized excitation wavelength of 386 nm was found to be close to unity for all doping concentrations.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…The possible non-radiative channels explained in Fig. 8 41,45,53 Further, the luminescence intensity ratio of yellow to blue (Y/B) is essential for white-light emission. The calculated (Y/B) ratio for the optimized excitation wavelength of 386 nm was found to be close to unity for all doping concentrations.…”
Section: +mentioning
confidence: 99%
“…25 These color coordinates are calculated from the PL emission spectra using x(λ), ȳ(λ) and z(λ) color matching functions defined in the CIE 1931. For a specified power spectral density P(λ), the degree of stimulation required to match the color of P(λ) is given by three equations:…”
Section: Colorimetric Theorymentioning
confidence: 99%
“…The photometric parameters are calculated by the spectrophotometric method using spectral energy distribution of CIE diagram. Dutta et al [48] reported that the tristimulus values X, Y, and Z can be estimated by the following equations, Table 1, which show an enhancement of x, y values in CIE diagram. All the color coordinates were extremely close to that of NSTC standard red color.…”
Section: Life Time Analysis and Photometric Characterizationmentioning
confidence: 99%
“…Traditional synthetic methods, such as microemulsion method [11], solid-state reaction [12], solvent/hydrothermal method [13], and microwave-assisted synthesis [14] etc., are often employed to prepare the luminescent materials. For example, CaMoO 4 thin films were obtained through complex polymerization method and annealed at high temperatures [15], while CaMoO 4 nanorods were also successfully fabricated via microwave irradiation assisted chelating agent method [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are inevitable to take some harsh reaction conditions, such as high temperature, special equipment or organic compound, which throw the practical application into a dilemma. Up to now, the co-precipitation method [18] has been widely used to synthesize meso-nano materials because of simple equipment, short time period and handy operation [13].…”
Section: Introductionmentioning
confidence: 99%